The Use of Antibiotics without a Prescription : a Literature Review - Dewi, Arie Kusumo; Handayani, Handayani; Febriani, Afira (Jurnal Medis Islam Internasional, 2022)
Background : Infectious diseases are treated with antibiotics. Antibiotics are widely used because infectious diseases are so common. Even though antibiotics are purchased at pharmacies with a doctor's prescription, many antibiotics are currently being taken without a prescription. Resistance will develop if antibiotics are consumed without a doctor's prescription and not according to indications for administration. Objective : This study examines how people use antibiotics without a doctor's prescription. Methods : The author of this article uses a method related to the article's title by using some relevant literature from database  of  journals such  as  Google  Scholar. The discussion and findings of this study will assist  readers and  health professionals in analyzing how people use antibiotics without a prescription. Result : Based  on  the  findings  of  the  five studies,   journals discuss   the relationship between knowledge level and attitudes regarding the use of antibiotics without a prescription. This  literature  review  shows that most people of reproductive age consume antibiotics without a doctor's prescription to treat symptoms usually caused by non-bacterial pathogens. Conclusion : . One of the intervention approaches taken to restrict access is government control. Holistic interventions against those who sell antibiotics without a prescription are expected to significantly reduce the irresponsible use of antibiotics in the community